Religious Meaning in Gorontalo Song Lyrics: A Barthesian Semiotic Study - Arni Nuruji; Herson Kadir; Zilfa Achmad Bagtayan (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study investigates religious meanings embedded in Gorontalo-language religious song lyrics through Roland Barthes’ three-tiered semiotic framework: denotation, connotation, and myth. Previous semiotic studies of Indonesian religious songs have focused primarily on national-language texts leaving a significant gap: no study has applied Barthes’ tripartite analysis to regional-language religious songs, particularly Gorontalo qasida, which uniquely integrate Islamic values with local cultural wisdom rooted in the philosophy of Adat Bersendikan Syara’, Syara’ Bersendikan Kitabullah. This research addresses that gap by combining Barthes’ semiotics with Glock and Stark’s religiosity dimensions as a classification framework. Employing a descriptive qualitative approach, data were drawn from 40 song lyrics across three albums by different Gorontalo singers, selected based on criteria of regional language use, religious theme, and symbolic content. The findings converge on three broad themes: (1) at the denotative level, lyrics function as a direct outreach medium conveying worship obligations, divine authority, and moral critique; (2) at the connotative level, they activate critiques of materialism, spiritual urgency, and Gorontalo cultural values such as respect for elders (hulawa) and communal solidarity (huyula); and (3) at the mythological level, five naturalized belief systems emerge salvation in the hereafter, faith and deeds as worth, death as homecoming, dignified death, and the prohibition of arrogance and greed. This study demonstrates that Gorontalo religious songs function as ideological texts for religious outreach, social control, and worldview formation, and offers a replicable methodological model for analyzing minority-language religious oral literature.